Analysis of Lactic Acid Levels in Breastmilk Before and After Storage at Room Temperature and Refrigerator Temperature - Titin Aryani; Dwi Ernawati (Jurnal Kesehatan, 2022)
Exclusive breastfeeding is the best source of food for babies under 6 months. Breast milk storage is thought to affect the components of the breastmilk. Research aim: to determine the levels of lactic acid in exclusive breast milk, both before and after storage at room temperature and refrigerator temperature. The study used experimental design with pre and posttest design. Lactic acid levels in breast milk were measured using an alkalimetric titration method. The selected breast milk storage temperature is room temperature (27-290 C), refrigerator temperature (2-40C), and the selected storage time is 0 and 4 hours. The sample were twenty (20) bottles of breastmilk from ten (10) breastfeeding mothers with a maximum lactation period of 6 months (exclusive breastfeeding) who live in Yogyakarta. The sampling technique was purposive sampling technique. The level of lactic acid in breast milk after storage at room temperature (27-290C) for 4 hours increased by 15.942%, while levels of lactic acid in breast milk after storage at refrigerator temperature (2-40C) for 4 hours increased as much as 2.309%. There is an increase in lactic acid levels of breast milk both after storage at room temperature and refrigerator temperature for 4 hours.